Monometallic/Bimetallic Co‐ZIFs Synthesis, Characterization, and Application for Adsorption of SO2 and CO2 in Continuous Flow System - Sumbal, Sara; Aslam, Zaheer; Irshad, Umar; Anwar, Sobia; Abbas, Aamir; Ahmad, Waqar; Hamza, Ali (Applied organometallic chemistry, 2024)
ABSTRACT Sulfur dioxide is serious ultimatum to human health as well as environment, while carbon dioxide is viewed as one of the primary drivers of the worldwide temperature alteration. Therefore, capturing of these gases is a dynamic research subject attracting much consideration from scientists. Herein, we report synthesis of a series of Co‐ZIF and bimetallic M‐Co‐ZIF adsorbents and application for room temperature adsorption of SO2 and CO2. In this work, the breakthrough curves for the adsorption of sulfur dioxide and carbon dioxide on Co‐ZIF and M‐Co‐ZIF were obtained experimentally and theoretically using a laboratory‐scale fixed bed column at room temperature. In this work, the adsorption capacities and breakthrough points for modified bimetallic M‐Co‐ZIF were found to be relatively higher than parent Co‐ZIF. Notably, a high SO2 uptake capacity of 7.1 mmol/g for Zr‐Co‐ZIF and high CO2 uptake capacity of 69.9 mmol/g for Ni‐Co‐ZIF were achieved. The parent cobalt and bimetallic ZIF materials were characterized by XRD, FTIR, SEM, and nitrogen physisorption. The XRD results confirm the formation of pure phase highly crystalline ZIF materials while BET analysis suggests high surface area of prepared adsorbents. Finally, the results of dynamic adsorption combined with characterization show great potential for preparation of bimetallic ZIF adsorbents for effective SO2 and CO2 adsorption. M‐Co‐ZIFs were synthesized for capturing SO2 and CO2 pollutant gases. The Zr‐Co‐ZIF and Mg‐Co‐ZIF showed SO2 and CO2 highest uptake capacities at room temperature, respectively. Experimental results were analyzed by a unique dual model approach. The dynamic modelling concludes that the uptake of SO2 follows chemisorption while CO2 showed physisorption mechanisms.